Life in Lockdown: Mental and Social Consequences of COVID-19 for differently able person (Journal of Namibian Studies : History Politics Culture, 2023)
The COVID-19 pandemic has created an unprecedented situation for populations worldwide, with consequences that are likely to persist for years. For persons with disabilities (PwDs), the disruption of training, therapy, classroom learning, and social interaction has brought profound challenges. This sudden shift has affected their social, biological, cognitive, and psychological well-being.This study examines the impact of COVID-19 on the mental health, social relationships, and physical activities of PwDs. A survey method was employed, involving 100 parents of children with disabilities selected purposively. Data were collected through a Google Form containing a five-point rating scale across three domains (mental health, physical activity, and social relationships), supplemented by open-ended questions. The findings revealed significant challenges: PwDs commonly experienced inattention, lack of concentration, boredom, inactivity, sleep disturbances, irritability, anger, and even weight gain. Many struggled to adjust to the prolonged “stay-at-home” conditions, finding the restrictions both difficult and distressing.